Prognostic value of activity patterns and stress measures for persistent pain and disability in acute neck pain: a 3-month follow-up study - Morf, Rita; Kernwein, Cyrill; Jaeger, Julia; Reicherzer, Leah; Degenfellner, Jürgen; Hotz-Boendermaker, Sabina (Frontiers in Pain Research, 2025)
BackgroundNeck pain (NP) represents a significant global health challenge, with a considerable proportion of individuals enduring persistent NP, which is associated with psychological stress. However, it remains unclear whether stress acts as a prognostic factor or emerges as a consequence of ongoing pain. An individual's behavioral response to pain, known as activity patterns (eustress persistence, distress persistence, activity pacing, and fear avoidance), reflects how individuals engage in daily activities and may influence both the experience and course of pain. These patterns have been linked to stress, potentially exacerbating pain intensity and disability. This study aims to investigate the prognostic value of activity patterns, subjective and objective stress in acute NP after three months. Furthermore, it examines the relationship between subjective and objective stress measures.MethodsThis study included participants (n = 125) with acute neck pain (NP) (<4 weeks). Baseline stress levels were measured objectively using hair cortisol concentration and subjectively using the Stress and Coping Inventory (SCI). Activity patterns were identified using the Avoidance-Endurance Fast Screen (AE-FS). Linear mixed models (LMM) were used to assess whether stress and activity patterns during the acute phase were prognostic factors for pain and disability three months later. A Pearson correlation was calculated between the subjective and objective stress measures.ResultsWeak correlations were found between subjective and objective stress measures. In the LMM, higher pain intensity during the acute NP phase was associated with increased pain intensity at 3-month follow-up. In terms of disability, both initial pain intensity and “stress due to uncertainty” were associated with higher disability after three months.DiscussionOnly a few consistent prognostic factors for persistent pain and disability have been identified, raising the question of whether current measures capture the most relevant aspects.Clinical Trial Registration:https://www.clinicaltrials.gov published 07/22, identifiers NCT05468684.